The Idea of Legal Reform Implementation Assessment Risks and Criminogenic Needs of Residivist Inmates in Overcoming Residivism - Darmawati, Darmawati; Nur, Rafika; Badu, Harun A. (UNISSULA, 2024)
The implementation of the development program for prisoners cannot be separated from the results of assessment recommendations carried out by correctional assessors, both risk assessments and needs assessments as stated in Law Number 22 of 2022 concerning Corrections. In carrying out the assessment, there are several obstacles in terms of substance, structure, infrastructure, culture and society so that the implementation of the guidance does not run optimally, resulting in recidivism. Every year, the number of recidivists at the Class II A Gorontalo Penitentiary increases. Through a case and conceptual approach, this research attempts to formulate a way to solve problems in terms of carrying out assessments for recidivist prisoners. Where the solution is to overcome this problem, a psychologist's assistance is needed in the assessment process to provide special treatment for them in order to create a more effective correctional system and provide protection, rehabilitation and reintegration for prisoners so that they do not repeat criminal acts.